2017
DOI: 10.1111/inm.12431
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of suicidal behaviour from the perspective of senior nursing undergraduate students

Abstract: The meaning ascribed to suicidal behaviours may influence the quality of the care provided to people at risk of suicide. Such a phenomenon has yet to be properly investigated amongst nursing undergraduate students, the aim of this study being to gain an understanding of the meanings of suicidal behaviour for a particular group of nurses. The study, which utilized grounded theory, was conducted in Brazil in 2016-2017 with 30 undergraduate students. The findings indicated that suicidal behaviour, classified acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…2013; Vedana & Zanetti 2019) and apprehension towards suicide (Scheckel & Nelson 2014; Vedana et al . 2018) experienced by some students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Vedana & Zanetti 2019) and apprehension towards suicide (Scheckel & Nelson 2014; Vedana et al . 2018) experienced by some students.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Vedana & Zanetti 2019), have reported being fearful and avoidant of interactions with people experiencing suicidal states (Scheckel & Nelson 2014; Vedana et al . 2018), and have negative attitudes towards suicide (Mamta et al . 2013; Vedana & Zanetti 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies across continents uncovered elements of the sociocultural context (e.g. religious beliefs, stigma, criminalization of suicide) that can influence the individuals' lived experiences of SI, the (student) nurses' attitudes towards suicide and suicide attempts and the (student) nurses' engagement in recognizing and discussing suicide (Flood et al, 2018;Osafo, Akotia, Boakye, & Dickson, 2018;Vedana et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%
“…A study conducted with Brazilian nursing students revealed that undergraduates consider suicidal behavior as complex and challenging (Vedana et al, 2017c). In addition, students reported that they want to avoid situations related to this topic as a form of self-protection, as well as pointed divergences between their own beliefs and the behaviors required in health care (Vedana et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%